Two new species of the genus Papillacarus (Acari: Oribatida: Lohmanniidae) from caves of Southern Vietnam - Ermilov, Sergey G.; Anichkin, Alexander E.; Wu, Donghui (Zootaxa, 2012)
An annotated checklist of oribatid mite taxa from three caves of Dong Nai Biosphere Reserve (Southern Vietnam) is pro-vided. We recorded 33 species, 29 genera and 16 families, of which 10 species, five genera and two families were foundin Vietnam for the first time. Three species, Malaconothrus variosetosus, Discoppia cylindrica and Machuella lineata, arefor the first time recorded from the Oriental region. Two new cave species of the genus Papillacarus are described. Papil-lacarus indistinctus sp. nov. is morphologically most similar to Papillacarus polygonatus Ermilov & Anichkin, however,it differs from the latter by the types of neotrichal setae, length of notogastral setae, morphology of some genital setae,epimeral setal formula, number of subcapitular setae m and palptarsal setae. P. polysetosus sp. nov. is morphologicallymost similar to Papillacarus jinggangshanensis Chen, Yang & Liang and P. konglinensis Chen & Yang, but differs fromboth by body size, body surface, length of certain notogastral setae, number of subcapitular setae m, and epimeral setal formula. An identification key to the Vietnamese species of Papillacarus is presented.